Determinants of Receptivity Towards Entomophagy among Young Adults - Ortiz Paniagua, Carlos Francisco; Bautista Hernández, Miguel Ángel; Lerch López , Paulina (Mercados y Negocios, 2024)
This research focuses on understanding the factors influencing the acceptance of entomophagy in Morelia, Michoacán. The study involves a survey aimed at two distinct groups of young adults aged 18 to 29 (control and experimental), a demographic known for being open to evolving food preferences. The results revealed interesting differences in preferences between individuals who have and have not tried insect-based foods. Surprisingly, the price did not emerge as a dominant influencing factor. The study suggests entomophagy can be a viable and accepted dietary option when relevant information is easily accessible, potentially reducing neophobia levels.